Penerapan PBL Berbasis Wordwall untuk Meningkatkan Hasil Belajar pada Materi Pubertas di Kelas VI - Asti Dwi Asih; Suci Perwita Sari; Mariani Rosmida Pakpahan (MASALIQ, 2025)
This study is motivated by the limited research on the application of the Problem Based Learning (PBL) model supported by Wordwall media in teaching puberty material, which holds significant potential to enhance learning outcomes for elementary school students. The objective of the study is to analyze the effect of implementing the PBL model integrated with Wordwall media on the activity and learning outcomes of sixth-grade students at SD Negeri 064966 Medan regarding puberty material. The research employed Classroom Action Research (CAR) with two cycles, involving 18 purposively selected students. Data were collected through observations of student activity, learning documentation, and learning outcome tests, and were analyzed descriptively and quantitatively. The results demonstrated significant improvements in student activity and learning outcomes from cycle I to cycle II, confirming the effectiveness of the PBL model supported by Wordwall media in enhancing student understanding. These findings align with constructivist learning theory, which emphasizes the active role of students in the learning process. In conclusion, the use of the Problem Based Learning model supported by interactive media contributes importantly to improving the quality of instruction and student learning outcomes. The study’s implications include enriching the literature on integrating PBL models and digital media, as well as recommendations for educators and educational institutions to optimize the use of interactive learning media. This research also opens opportunities for further studies on the impact of other digital media across various elementary school subjects.